Psychological characteristics of manifestation of internet addiction in teen-age - Meloyan А. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2014)
The article provides theoretical analysis and experimental study which reveal the psychological characteristics of manifestation of internet addiction in teen-age. Author mark some factors negatively influencing on psychological autonomy from internet space in adolescence.